Pengaruh Penerapan Model Pembelajaran Learning Cycle 5E Terhadap Pemahaman Konsep Matematis Peserta Didik Kelas VII SMPN 1 Lembah Gumanti - TAUFIKURAHMAN . (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematical concept understanding is onenof the goals from mathematical learning that must owned by students. However, acording to result of the test that given in Junior High School 1 Lembah Gumanti showed the low students mathematical concept understanding. This could be improved by implement learning cycle 5E model. The purpose of this research  is to know and to discribe the improvement of mathematical concept understanding of student who’s learning using learning cycle 5E model and to know and to discribe wether the mathematical concept understanding of students who’s learning with learning cycle 5E model is better than mathematical concept understanding of student who’s learning with direct instrution in class VII junior high school 1 Lembah Gumanti. This researchnis a combinationnof quasy experimen and deskriptiv research withnresearch design is The Nonequivalent Posttest-OnlycControl GroupnDesign. Based on the result of quizzes there are improvement of mathematical concept understanding of student who’s learning with learning cycle 5E model, and based on the result of hypothesis test, the mathematical concept understanding of student who’s learning with learning cycle 5E model are better than the mathematical concept understanding of student who’s learning with direct instuction.  That can be conclude that laerning cycle 5E model is influences students mathematical concept understanding. Keywords – Mathematical Concept Understanding, Learning Cycle 5E Model.